Autonomous Goal Following for Quadruped Robot using Fuzzy Proportional Control - Lopez Ramos , Jose Eduardo; Castillo, Oscar; Melin, Patricia (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
In this paper a fuzzy Proportional (PD) Controller was designed and implemented for dynamically adapting the velocity and motion parameters in a quadruped robot for autonomously following a goal. The FNK0050 Freenove quadruped robot was utilized for the experiments, which has 12 degrees of freedom and this is why it has higher complexity. Experimental results show that the proposed fuzzy PD controller surpasses the standard PID controller provided as default by the manufacturer of the robot.